Community-dwelling older people hospitalised for fall-related injury: characterising high length of stay users. (7th October 2012) - Vu, T; Finch, C; Day, L
Abstract : Background: Nearly half to 60% of falls in community-dwelling older people aged 65+ years result in physical injuries and 20%–50% of these require medical attention, including emergency department visit and hospitalisation. Fallers who stay in hospital longer than would be expected based on the primary injury diagnosis create an excess financial burden on the health system and represent a priority target group for fall prevention. Objectives: To identify and characterise high-length-of-stay (HLOS) patients among community-dwelling older people aged 65+ years hospitalised for fall-related injury. Methods: We analysed hospital discharge data from Victoria, Australia, to identify and characterise HLOS patients among community-dwelling older people aged 65+ years hospitalised for fall-related injury. We defined an episode as HLOS if the length of stay (LOS) was more than three times the average LOS for a particular diagnosis-related group. Results: Between 2005/06 and 2007/08 6822 patients (14.2% of the study group of which 73.8% were women) had ≥1 episode classified as HLOS. The HLOS patients accounted for 19.9% of episodes and 39.9% of bed days. HLOS patients were similar to non-HLOS patients in terms of indigenous status, in-hospital mortality and ethnicity. However, HLOS patients were older, less likely to be married, less likely to have hospital insurance and more likely to have comorbidity than non-HLOS patients. Significance/Contribution to the Field: This study identifies priority groups for a targeted prevention approach.